In sight : contemporary Dutch photography from the collection of the Stedelijk Museum Amsterdam - Ehlers, Carol; Visser, Hripsimé; Art Institute of Chicago, Chicago (Amsterdam : Stedelijk Museum Amsterdam, 2005)
Aarsman, Hans ; van der Meer, Hans ; Berger, Wout ; Dijkstra, Rineke ; Breukel, Koos ; van Balen, Céline ; van Manen, Bertien ; Deroo, Wijnanda ; Kaap, Gerald Van Der ; Hondius, Juul ; Diederix, Elspeth ; Goossens, Marnix ; van Meene, Hellen
Publication on the occasion of the exhibition 'In sight: contemporary Dutch photography from the collection of the Stedelijk Museum Amsterdam at the Art Institute of Chicago in Chicago, 26.03.2005-08.05.2005
boek